State legislative committee deliberations: Why some issues are difficult and where state legislators turn for help. (31st August 2021) - Taylor, Kristin; Sarbaugh‐Thompson, Marjorie; Betz, Steven
Abstract: Objective: This study explores why state legislators think some issues are difficult and where they turn for help with these issues. Methods: We use content analysis of legislators' interview responses to identify sources of difficulty that arose during committee deliberations. Results: Many legislators say that issues are difficult because of committee and caucus politics, technical information, interest group pressure, jurisdictional competition, and budget constraints. We find few associations between sources of difficulty and legislator characteristics or institutional context. Mundane issues are often seen as difficult, with culture war issues rarely mentioned. Using cluster analysis, we identify five major categories of issue difficulty. We find that legislators grapple with these categories of difficulty by relying on interest groups, partisan staff, and committee members rather than on caucus leaders, the governor, or their voters. Conclusion: These findings contribute to our understanding of impediments to policy making that legislators navigate in legislative committees.